An Econometric Analysis of Global Muslim Travel Index: A Study on the Perspectives of Permitted Tourism Industry in the Global Context - Nisthar, Sainudeen; Mustafa, Abdul Majeed Mohamed (International Journal of Economics and Financial Issues, 2019)
The prime objective of this study is to assess the relationship between rank of Global Muslim Travel Index (GMTI) and the services composed into Global Muslim Travel Index (GMTI) such as Prayers Places (PRPL), Airport Facilities (AIRP), Unique Experiences (UNIQ), Hotel (HOTE), and Restaurant (REST) which are the independent variables. Cross sectional quantitative data of 30 countries connected to components of the Permitted tourism services are collected from the Institution of Crescent Rating 2018. The dependent variable is RANK: Global Rank of global Muslim Travel Index (GMTI) - 2018. The prime tools used in this study are Correlation, ANOVA, Multiple Regression, Histogram, and PP-Plot. It is found that As Hotel (HOTE): hotel facilities are increased by one unit, Global Rank of global Muslim Travel Index (RANK) of the respective country is lowered by 0. 352. Inverse linear relationship between Global Rank of GMTI 2018 and other factors are significantly estimated in the different degrees of strength. Keywords: Global Muslim Travel Index, Global Rank, Permitted Tourism, Regression JEL Classifications: F01, L83, Z32 DOI: https://doi.org/10.32479/ijefi.8537